Global strategies, differing experiences. Electricity companies in two late-industrialising countries: Spain and Argentina, 1890–1950 - Lanciotti, Norma Silvana (2014)
The article compares the performance and profitability rates of electric utility firms in Spain and Argentina from the early period of global electrification to the period following World War 2. It aims to analyse the relationship between the investment strategies of international electricity companies and local conditions in two lateindustrialising countries, and evaluate its impact on the structure and development of both electric utility systems. The study finds similar long-term trends in profitability as a result of the global strategies of multinational holding companies; nonetheless profitability rates varied greatly from one country to another. Rates were higher in Argentina as foreign firms controlled large systems in most dynamic urban areas. In contrast, the increasing investment of local firms in electric utilities paved the way to a less profitable but more equitable electricity system in Spain